2014
DOI: 10.3390/nu6093403
|View full text |Cite
|
Sign up to set email alerts
|

Does Sufficient Evidence Exist to Support a Causal Association between Vitamin D Status and Cardiovascular Disease Risk? An Assessment Using Hill’s Criteria for Causality

Abstract: Serum 25-hydroxyvitamin D (25(OH)D) levels have been found to be inversely associated with both prevalent and incident cardiovascular disease (CVD) risk factors; dyslipidemia, hypertension and diabetes mellitus. This review looks for evidence of a causal association between low 25(OH)D levels and increased CVD risk. We evaluated journal articles in light of Hill’s criteria for causality in a biological system. The results of our assessment are as follows. Strength of association: many randomized controlled tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 118 publications
1
34
0
6
Order By: Relevance
“…Cardiovascular disease (CVD) incidence and prevalence was found to increase with low serum 25(OH)D levels according to Weyland et al (2014). The authors demonstrated an inverse association between 25(OH)D levels and CVD risk factors in various populations, locations and circumstances (Weyland et al 2014).…”
Section: Vitamin D Functions In a Human Bodymentioning
confidence: 98%
See 1 more Smart Citation
“…Cardiovascular disease (CVD) incidence and prevalence was found to increase with low serum 25(OH)D levels according to Weyland et al (2014). The authors demonstrated an inverse association between 25(OH)D levels and CVD risk factors in various populations, locations and circumstances (Weyland et al 2014).…”
Section: Vitamin D Functions In a Human Bodymentioning
confidence: 98%
“…Cardiovascular disease (CVD) incidence and prevalence was found to increase with low serum 25(OH)D levels according to Weyland et al (2014). The authors demonstrated an inverse association between 25(OH)D levels and CVD risk factors in various populations, locations and circumstances (Weyland et al 2014). Autier and Gandini (2007) in the meta-analysis of randomized, controlled trials demonstrated a decrement in mortality from cardiovascular events in approximately 7 % of subjects using vitamin D supplements.…”
Section: Vitamin D Functions In a Human Bodymentioning
confidence: 98%
“…The 'Bradford Hill Criteria', first published over fifty years ago, are a recognized and widelyused framework against which epidemiological studies may be examined to consider whether a causal interpretation of an observed association is valid [40,41]. In this vein, these guidelines have been widely used in the public health arena to explore whether causal links exist between an exposure of interest and a behaviour or health outcome [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Participants were stratified into two groups, with and without MetSyn, based on NCEP -ATP III criteria (Weyland et al, 2014) …”
Section: The Diagnosis Of Metabolic Syndromementioning
confidence: 99%